2021
DOI: 10.1007/s10562-021-03737-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Magnetic Moment on Single Atom Catalytic Activation Energy Barriers

Abstract: Design of the molecular environment of single atom catalysts (SAC) is promising for achieving high catalytic activity without expensive and scarce platinum-group metals (PGM). We utilize a first principles approach to examine how the spin state of the SAC and reactants can affect catalytic energy barriers of V, Fe, Mo, and Ta on two different graphene defects with differing magnetic moments. Spin polarized projected density of states and climbing image nudged elastic band calculations demonstrate relatively lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Previously studied N-doped ZGNRs edges were established as magnetic [26], different from our findings for FeN 4 -doped ZGNR edges. Other DFT studies have reported on the spin suppression of edge carbon sites in Ti-, Pt-, and Au-doped ZGNR edges [52][53][54]. The band structures depicted in Figure 4b also exhibited sensitivity to the FeN 4 location, which was especially noticeable in the spin-down channel (red curves in Figure 4b).…”
Section: Magnetic and Electronic Properties As A Function Of Fen4 Loc...mentioning
confidence: 74%
See 2 more Smart Citations
“…Previously studied N-doped ZGNRs edges were established as magnetic [26], different from our findings for FeN 4 -doped ZGNR edges. Other DFT studies have reported on the spin suppression of edge carbon sites in Ti-, Pt-, and Au-doped ZGNR edges [52][53][54]. The band structures depicted in Figure 4b also exhibited sensitivity to the FeN 4 location, which was especially noticeable in the spin-down channel (red curves in Figure 4b).…”
Section: Magnetic and Electronic Properties As A Function Of Fen4 Loc...mentioning
confidence: 74%
“…Previously studied N-doped ZGNRs edges were established as magnetic [ 26 ], different from our findings for FeN 4 -doped ZGNR edges. Other DFT studies have reported on the spin suppression of edge carbon sites in Ti-, Pt-, and Au-doped ZGNR edges [ 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spin degrees of freedom have an important in uence on the catalytic performance of magnetic monatomic catalysts 47,48,49,50 . The spin density population of M 1 /PTA are presented in Fig.…”
Section: Screening M1/pta Catalysts For Ethyne Hydrogenation Reactionmentioning
confidence: 99%